Business model canvas of auto detailing and car wash home service - Ekawati, Ratna; Prawira, Ardenta Toga; Saptiyadi, Arif; Hapsari, Ayuningtyas Woro; Prihasetya, Galih; Sayputra, Marco (Universitas Sultan Ageng Tirtayasa, 2024)
A general supplier and service provider for office goods, air conditioners, and office car maintenance services plans to explore a new service sector: home service auto detailing. Due to the rapid growth of the home service business since the COVID-19 pandemic, it is necessary to analyze the car auto detailing business model to enable design and improvements. This study designs the business model using the business model canvas approach. The research begins by benchmarking several existing car auto detailing businesses using data from literature studies to understand their business models. The business environment is analyzed through observations, collecting data on the aspirations of business owners, and gathering customer profiles by distributing questionnaires to consumers. The result of this research is a proposed business model incorporating a business model canvas, SWOT analysis, and BPMN diagram using the SAP Power Designer approach, along with a proposed booking application software using PIECES analysis.